Basic finance : - Mayo, Herbert B. (Thomson, 2007)
BASIC FINANCE: AN INTRODUCTION TO FINANCIAL INSTITUTIONS, INVESTMENTS, AND MANAGEMENT uses a proven "modular" approach to help you learn finance concepts quickly and easily. Plus, this edition is enhanced with numerous Internet references, calculator exercises, and tie-ins with Microsoft ® Excel, so you'll be on your way to using the technologies professionals use in the corporate world every day.